(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Artificial Intelligence (AI) is gaining importance as an innovative approach in education. Introducing AI into Uzbek schools by 2030 can improve learning quality, enable personalized programs, and enhance students’ intellectual capacity. Teacher training, curriculum adaptation, and infrastructure development remain crucial. The paper explores the effectiveness, practical application, and future prospects of AI in the educational system.